The Value of Sustainability: How Environmental, Social, and Governance Cost Investments Impact Corporate Financial Performance - He, Lu (American Journal of Business Science Philosophy, 2024)
This study aims to explore the impact of environmental, social, and governance (ESG) cost investment on corporate financial performance, using sustainable development theory, stakeholder theory, and agency theory as a comprehensive theoretical framework to clarify the definition and measurement standards of ESG cost investment (including environmental, social, and governance expenditures). The ESG cost investment data comes from the annual reports, sustainable development reports, or social responsibility reports released by listed companies, and return on assets and return on equity are selected as financial performance indicators for enterprises. The findings indicate that ESG cost investment, as well as environmental investment, social responsibility investment, and governance investment, have a positive impact on corporate financial performance. In addition, the study also considered corporate ownership structure and industry-specific factors to understand how ESG cost investment affect business performance in different contexts. By studying enterprise heterogeneity and industry-specific dynamics, this study aims to provide tailored management recommendations for enterprises in different ownership and industries. This study aims not only to contribute to academic discussions on corporate sustainability, but also to provide practical significance for businesses and investors by emphasizing the financial benefits of strategic ESG investments.
Keywords: investment; environment; governance; social; sustainability; corporate finance